Ground and satellite-based observations of ionospheric plasma bubbles and blobs at 5.65° latitude in the Brazilian sector. Issue 8 (15th April 2021) - Agyei-Yeboah, Ebenezer; Roberto Fagundes, Paulo; Tardelli, Alexandre; Pillat, Valdir Gil; Pignalberi, Alessio; Kavutarapu, Venkatesh; Pezzopane, Michael; Vieira, Francisco
Highlights: Ground- and satellite-based observation of plasma bubbles/blobs and atypical ESF. Atypical ESF are associated with bubbles and blobs incidence in nightglow images. F-layer reflections are different from first F-layer reflections when atypical ESF is present. Abstract: This investigation uses simultaneous observations from all-sky imager system and an ionosonde collocated at Araguatins (5.65° S, 48.07° W and dip-latitude of 4.17° S), a near-equatorial region in Brazil. These simultaneous observations were used to investigate the occurrence of plasma bubbles and blobs in the field of the imaging system and their association with atypical range Spread-F signature in ionograms. Also, in-situ observation of plasma density from Swarm satellites were used to support the ground-based observations. Using a few cases, a methodology will be established to identify in the plasma blobs (atypical ESF) in the ionograms when there is the simultaneous observation of plasma bubbles and blobs in the field of view of the ionosonde. For this purpose, simultaneous sequence of OI 630.0 nm nightglow images and ionograms are presented for different case studies; 1. when there is the absence of a plasma bubble or blob, 2. when there is only the occurrence of plasma bubbles and 3. when there is the occurrence of plasma bubbles and blobs, in order to compare traces in the ionogram in all these case studies. With these we can cover all kinds of signatures in the ionograms corresponding to no irregularities, plasma bubbles only and plasma bubbles-blobs. These OI 630.0 nm nightglow and ionograms recorded simultaneously make it possible to establish a novel methodology to recognize in ionograms cases when there is the occurrence of Spread-F signature associated with bubble-blob in the FOV of the ionosonde.